Answer:
(x - 4)(x^2 + 7)
Step-by-step explanation:
x^2 is a factor of the first two terms: x^3 - 4x^2 = x^2(x - 4).
7 is a factor of the last two terms: 7(x - 4).
Note how (x - 4) is a factor of the entire four-term expression given above.
Then: x^3-4x^2+7x-28 = (x - 4)(x^2 + 7)
Answer:
(3a + 2)(a + 3)
Step-by-step explanation:
Check the picture below.
the triangle is an isosceles, so it has twin legs, and a base bottom.
the twin sides stem from the "vertex", and we know the vertex is 120°, and since the triangle is inscribed in a circle, because the circle is "circumscribing" it, then the base side of the triangle will be the diameter of it.
if we run a perpendicular line to the base from the vertex, we'll split the vertex in two 60° angles, as you see there, giving us a 30-60-90 triangle on each side.
so, anyhow, the rest is just a matter of using the 30-60-90 rule.
that's the diameter, and as you know, the radius is just the length of the base, or half the diameter.
Answer: 10
Step-by-step explanation: 10 divided by 5 is 2. 2 times 2 is 4
V=900m³
V=L*w*h
V=20*3*w
V=60*w
60*w=900
w=900/60
w=15m